Antonyan Yu., Muradyan H., Gabrielyan L., Safaryan A. Review of the collective monograph "Between Imperial and Post-Imperial: Developments of the Armenian Religious Landscape in the 20th Century" - Kharatyan, Hranush (History and Culture, 2025)
The review is discussing the collective monograph "Between Imperial and Post-Imperial: The development of Armenia’s Religious Landscape in the 20th Century," published in 2023 and consisting of ten chapters. The authors of the book are Yu. Antonyan, G. Muradyan, L. Gabrielyan, and A. Safaryan. The study examines religious processes in the territory of modern-day Armenia that have shaped the Armenian cultural landscape from the imperial period to the era of independent Armenia.Various chapters of the book analyze Armenia’s religious diversity during the imperial, Soviet, and post-Soviet periods, including transformations in the religious and cultural identity of Armenian Catholics, Evangelicals, several ethno-religious communities (Molokans, Assyrians, Yezidis), as well as representatives of new religious movements.The book offers a fresh perspective on religious developments over the past two centuries, raising important questions that could spark scholarly debates among specialists and the wider public alike.